Identifying hotspots and management of critical ecosystem services in rapidly urbanizing Yangtze River Delta Region, China. (15th April 2017) - Cai, Wenbo; Gibbs, David; Zhang, Lang; Ferrier, Graham; Cai, Yongli
Abstract: Rapid urbanization has altered many ecosystems, causing a decline in many ecosystem services, generating serious ecological crisis. To cope with these challenges, we presented a comprehensive framework comprising five core steps for identifying and managing hotspots of critical ecosystem services in a rapid urbanizing region. This framework was applied in the case study of the Yangtze River Delta (YRD) Region. The study showed that there was large spatial heterogeneity in the hotspots of ecosystem services in the region, hotspots of supporting services and regulating services aggregately distributing in the southwest mountainous areas while hotspots of provisioning services mainly in the northeast plain, and hotspots of cultural services widespread in the waterbodies and southwest mountainous areas. The regionalization of the critical ecosystem services was made through the hotspot analysis. This study provided valuable information for environmental planning and management in a rapid urbanizing region and helped improve China's ecological redlines policy at regional scale. Highlights: A comprehensive framework to identify hotspots of critical ecosystem services was developed. The framework comprised five core steps. The framework was applied in the Yangtze River Delta Region. Regionalization and management strategies of the YRD Region were suggested.